Generic vancomycin enriches resistant subpopulations of Staphylococcus aureus after exposure in a neutropenic mouse thigh infection model (2012)
ABSTARCT: "Previous studies have shown that ""bioequivalent"" generic products of vancomycin are less effective in vivo against Staphylococcus aureus than the innovator compound. Considering that suboptimal bactericidal effect has been associated with emergence of resistance, we aimed to assess in vivo the impact of exposure to innovator and generic products of vancomycin on S. aureus susceptibility. A clinical methicillin-resistant S. aureus (MRSA) strain from a liver transplant patient with persistent bacteremia was used for which MIC, minimum bactericidal concentration (MBC), and autolytic properties were determined. Susceptibility was also assessed by determining a population analysis profile (PAP) with vancomycin concentrations from 0 to 5 mg/liter. ICR neutropenic mice were inoculated in each thigh with ∼7.0 log(10) CFU. Treatment with the different vancomycin products (innovator and three generics; 1,200 mg/kg of body weight/day every 3 h) started 2 h later while the control group received sterile saline. After 24 h, mice were euthanized, and the thigh homogenates were plated. Recovered colonies were reinoculated to new groups of animals, and the exposure-recovery process was repeated until 12 cycles were completed. The evolution of resistance was assessed by PAP after cycles 5, 10, 11, and 12. The initial isolate displayed reduced autolysis and higher resistance frequencies than S. aureus ATCC 29213 but without vancomycin-intermediate S. aureus (VISA) subpopulations. After 12 cycles, innovator vancomycin had significantly reduced resistant subpopulations at 1, 2, and 3 mg/liter, while the generic products had enriched them progressively by orders of magnitude. The great capacity of generic vancomycin to select for less susceptible organisms raises concerns about the role of therapeutic inequivalence of any antimicrobial on the epidemiology of resistance worldwide. Estudios previos han demostrado que los productos genéricos ""bioequivalentes"" de la vancomicina son menos eficaces in vivo contra Staphylococcus aureus que el compuesto innovador. Teniendo en cuenta que el efecto bactericida subóptimo se ha asociado con la aparición de la resistencia, nuestro objetivo fue evaluar in vivo el impacto de la exposición a los productos innovadores y genéricos de vancomicina sobre la susceptibilidad a S. aureus. Se utilizó una cepa de S. aureus resistente a la meticilina (MRSA) clínica de un paciente trasplantado de hígado con bacteriemia persistente para la cual se determinaron la concentración microbiana mínima (MBC) y las propiedades autolíticas. La susceptibilidad también se evaluó determinando un perfil de análisis de población (PAP) con concentraciones de vancomicina de 0 a 5 mg / litro. ICR ratones neutropénicos se inocularon en cada muslo con ~ 07.0 log (10) CFU. El tratamiento con los diferentes productos de vancomicina (innovador y tres genéricos: 1,200 mg / kg de peso corporal / día cada 3 h) comenzó 2 h más tarde, mientras que el grupo control recibió solución salina estéril. Después de 24 h, los ratones se sometieron a eutanasia, y los homogenados de los muslos se plaquearon. Las colonias recuperadas fueron reinoculadas a nuevos grupos de animales, y el proceso de exposición-recuperación se repitió hasta completar 12 ciclos. La evolución de la resistencia fue evaluada por PAP después de los ciclos 5, 10, 11 y 12. El aislamiento inicial mostró una autolisis reducida y frecuencias de resistencia más altas que S. aureus ATCC 29213 pero sin subunidades de S. aureus (VISA) intermedio de vancomicina. Después de 12 ciclos, el innovador vancomicina había reducido significativamente las subpoblaciones resistentes a 1, 2 y 3 mg / litro, mientras que los productos genéricos los habían enriquecido progresivamente por órdenes de magnitud. La gran capacidad de la vancomicina genérica para seleccionar organismos menos sensibles plantea preocupaciones sobre el papel de la inequivalencia terapéutica de cualquier antimicrobiano en la epidemiología de la resistencia en todo el mundo. "